Person-centred care for dementia patients (front-end Android application development) - Siti Nur Umm'aira Phang Binte Muhammed Imran (Nanyang Technological University, 2024)
Dementia is prevalent in the world. Caregivers of people living with dementia are essential to help contain the symptoms of the disease. In the process of caring for them, caregivers face a lot of stress. PErson-centred cARe (PEAR) is a system created to alleviate the burden on the staff in a dementia care centre. Its purpose is to aid in the managing of a dementia care centre, its patients and activities, as well as enhance communication between the doctors, supervisors, caregivers, game therapists and administrators. It has gone through several batches of developers over the years, however it is still in development. For the mobile application, there are still missing features and room for improvement in terms of UI and UX. The objective of this project is to improve UI and UX of the mobile application, as well as fix bugs and continue tracking progress of the project.